2023
DOI: 10.21037/jtd-23-38
|View full text |Cite
|
Sign up to set email alerts
|

The association of coagulation indicators with in-hospital acute kidney injury and malignant events of patients with acute aortic dissection: a retrospective cohort study

Abstract: Background: Acute kidney injury (AKI) is a prevalent complication of acute aortic dissection (AAD) and is associated with poor outcomes. The onset of AAD may result in endothelial injury due to the formation of the false lumen, which can activate the coagulation pathway and lead to coagulation dysfunction. It serves as a valuable diagnostic and prognostic marker for AAD, but also plays a role in the pathological mechanisms underlying AKI. We aimed to investigate the potential value of coagulation indicators at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Jain and Reilly (2019) explains this phenomenon by stating that clotting factors such as factor VII, involved in the extrinsic pathway, are not principally cleared in the renal system [16] . Despite the present study indicating that prothrombin time may not be a significant indicator of coagulation abnormalities in renal failure patients, some studies have indicated that it can be a significant indicator, especially in patients with end-stage chronic kidney disease in the setting of coagulopathy [13] . The difference in the research findings can be explained by the small sample size used in the present study and the deliberate prohibition of patients on treatment plans that may affect the PT levels from the sample study.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Jain and Reilly (2019) explains this phenomenon by stating that clotting factors such as factor VII, involved in the extrinsic pathway, are not principally cleared in the renal system [16] . Despite the present study indicating that prothrombin time may not be a significant indicator of coagulation abnormalities in renal failure patients, some studies have indicated that it can be a significant indicator, especially in patients with end-stage chronic kidney disease in the setting of coagulopathy [13] . The difference in the research findings can be explained by the small sample size used in the present study and the deliberate prohibition of patients on treatment plans that may affect the PT levels from the sample study.…”
Section: Discussioncontrasting
confidence: 90%
“…As a result, these patients have increased rates of bleeding which are thought to be driven principally by platelet dysfunction, low production of clotting factors, and anticoagulants with pharmacokinetic profile changes of the compounds that affect blood clotting mechanisms [10] . This study contributes to the existing studies on the relationship between renal failure and coagulation abnormalities and complications by investigating and highlighting PTT levels as a significant indicator of the severity and prognosis of the disease [11][12][13][14] . Regarding PT levels, there were no significant statistical differences between renal patients and control samples.…”
Section: Discussionmentioning
confidence: 99%